Bamboo Shark as a Small Animal Model for Single Domain Antibody Production - Wei, Likun; Wang, Meiniang; Xiang, Haitao; Jiang, Yuan; Gong, Jinhua; Su, Dan; Al Azad, M. A. R.; Dong, Hongming; Feng, Limin; Wu, Jiajun; Chan, Leo Lai; Yang, Naibo; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
The development of shark single domain antibodies (sdAbs) is hindered by the high cost and tediousness of large-sized shark farming. Here, we demonstrate white-spotted bamboo sharks (Chiloscyllium plagiosum) being cultivated commercially as a promising small animal model to produce sdAbs. We found that immunoglobulin new antigen receptor (IgNAR) presented in bamboo shark genome, transcriptome and plasma. Four complete IgNAR clusters including variable domains (vNARs) were discovered in the germline and the Variable-Joining pair from IgNAR1 cluster were dominant from immune repertoires in blood. Bamboo sharks developed effective immune responses upon green fluorescent protein (GFP), near-infrared fluorescent protein iRFP713 and Freund’s adjuvant immunization revealed by elevated lymphocyte counts and antigen specific IgNAR. Before and after immunization, the complementarity determining region 3 (CDR3) of IgNAR were the major determinant of IgNAR diversity revealed by 400-bp deep sequencing. To prove that bamboo sharks could produce high affinity IgNAR, we isolated anti-GFP and anti-iRFP713 vNARs with up to 0.3 nM and 3.8 nM affinities respectively from immunized sharks. Moreover, we constructed biparatopic vNARs with the highest known affinities (20.7 pM) to GFP and validated the functions of anti-GFP vNARs as intrabodies in mammalian cells. Taken together, our study will accelerate the discovery and development of bamboo shark sdAbs for biomedical industry at low cost and easy operation.